The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s13018-019-1460-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of MRA and MRI for the bursal-sided partial-thickness rotator cuff tears: a meta-analysis

Abstract: Background Numerous quantitatively studies have focused on the diagnosis of bursal-sided partial-thickness rotator cuff tears (RCTs); however, the accuracy of magnetic resonance imaging (MRI) and MR arthrography (MRA) remains inconclusive. This study was performed systematically to compare the diagnostic value of MRA and MRI for the bursal-sided partial-thickness RCTs. Methods Three electronic databases, PubMed, Embase, and Cochrane Library, were utilized to retrieve articles comparing the diagnostic value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…22 Magnetic resonance arthrography has superior diagnostic value in terms of sensitivity and specificity for articular-sided PRCTs compared with ultrasonography and MRI, although similar diagnostic accuracy has not been found for bursal-sided tears. 23…”
Section: Figurementioning
confidence: 99%
“…22 Magnetic resonance arthrography has superior diagnostic value in terms of sensitivity and specificity for articular-sided PRCTs compared with ultrasonography and MRI, although similar diagnostic accuracy has not been found for bursal-sided tears. 23…”
Section: Figurementioning
confidence: 99%
“…Based on the depth of the tears, rotator cuff tears are classified as either partial‐thickness rotator cuff tears (PTRCTs) or full‐thickness rotator cuff tears 3 . According to previous imaging and cadaveric studies, the prevalence of PTRCTs ranges from 13% to 37% 4,5 . Because the remaining intact tendon fibers are under greater tension than normal, PTRCTs sometimes cause more significant pain and dysfunction than full‐thickness rotator cuff tears 6 …”
Section: Introductionmentioning
confidence: 99%
“…3 According to previous imaging and cadaveric studies, the prevalence of PTRCTs ranges from 13% to 37%. 4,5 Because the remaining intact tendon fibers are under greater tension than normal, PTRCTs sometimes cause more significant pain and dysfunction than full-thickness rotator cuff tears. 6 PTRCTs can be further classified into articular-side, intratendinous, and bursal-side tears based on the specific location of the tears.…”
Section: Introductionmentioning
confidence: 99%
“…Pain intensity is directly correlated with the presence of kinesiophobia. Recently, multiple studies [ 11 , 12 ] have focused on the shoulder pain caused by partial-thickness rotator cuff tears, and indicated that compared with interstitial and articular-sided partial-thickness RCTs, bursal-sided tears can result in more severe shoulder pain. However, the effect of kinesiophobia on postoperative function was not evaluated.…”
Section: Introductionmentioning
confidence: 99%